APPLICATION OF THE PRINCIPLE OF PROPORTIONALITY IN THE IMPOSITION OF PUNISHMENT AGAINST PERPETRATORS OF CRIMINAL OFFENSES - Sofyan, Ade (Hukum Responsif, 2024)
The judge's consideration is an important thing in the imposition of punishment, so it is necessary to conduct a deeper review of the suitability between the amount of punishment and the consideration used by the judge, because the judge's consideration has a major influence on the proportionality of the imposition of punishment and the determination of the severity of the punishment, with this it is hoped that the punishment given has fulfilled a sense of justice for all parties. This study aims to determine the factors considered by the judge in the imposition of punishment and the proportionality of the imposition of punishment in cases of negligence that causes death and injury to others. The research method used is normative juridical which is descriptive (describing) with a research approach in the form of a statute approach and case approach. The result of the research shows that there are several objectives in imposing punishment commensurate with the fault of the perpetrator which considers the same importance between public protection, general prevention and special prevention. However, in the development of discourse on the imposition of punishment, the position of proportionality as a limiting principle is not only followed by the preventive view, but also adopted by the modern retributive variant. This is influenced by different perspectives in viewing the principle of proportionality. From a positive understanding of the principle of proportionality, the court is obliged to impose a punishment that is commensurate with the criminal offence. To that end, the court determines the severity of the punishment to be imposed based on the criminal offence.